2015
DOI: 10.1007/s12010-015-1661-8
|View full text |Cite
|
Sign up to set email alerts
|

Production of Xylitol from d-Xylose by Overexpression of Xylose Reductase in Osmotolerant Yeast Candida glycerinogenes WL2002-5

Abstract: Efficient bioconversion of D-xylose into various biochemicals is critical for the developing lignocelluloses application. In this study, we compared D-xylose utilization in Candida glycerinogenes WL2002-5 transformants expressing xylose reductase (XYL1) in D-xylose metabolism. C. glycerinogenes WL2002-5 expressing XYL1 from Schefferomyces stipitis can produce xylitol. Xylitol production by the recombinant strains was evaluated using a xylitol fermentation medium with glucose as a co-substrate. As glucose was f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(4 citation statements)
references
References 41 publications
0
3
0
1
Order By: Relevance
“…Endogenous genes for xylose utilization, including genes for xylose reductase (XYL1) and xylose kinase (XKS1), are present in C. glycerinogenes . In our previous study, the strain CGWT was fermented in YPX medium for 84 h. Moreover, the OD 600 reached 2.8, but the xylose concentration did not decrease, which indicated that xylose was not utilized (Figure S4).…”
Section: Resultsmentioning
confidence: 92%
“…Endogenous genes for xylose utilization, including genes for xylose reductase (XYL1) and xylose kinase (XKS1), are present in C. glycerinogenes . In our previous study, the strain CGWT was fermented in YPX medium for 84 h. Moreover, the OD 600 reached 2.8, but the xylose concentration did not decrease, which indicated that xylose was not utilized (Figure S4).…”
Section: Resultsmentioning
confidence: 92%
“…Pemilihan ragi untuk fermentasi merupakan hal yang penting dalam proses fermentasi xilitol. Beberapa strain ragi digunakan untuk produksi xilitol, yaitu Candida tropicalis (Misra dan Raghuwanshi., 2012;Rao et al, 2006), C. guilliermondii (Arruda et al, 2017), C. glycerinogenes (Zhang et al, 2015), C. mogii (Tochampa et al, 2005), Rhodotorula mucilaginosa (Vajzovic et al, 2012), Pichia pastoris (Cheng et al, 2014), Yamadazyma ubonensis (Junyapate et al, 2014), Scheffersomyces amazonensis (Cadete et al, 2016), dan Meyerozyma caribbica Y67 (Saputra et al, 2020). Saccharomyces cerevisiaestrain asli tidak dapat memfermentasi gula xilosa untuk membentuk xilitol, namun dengan memasukkan gen penyandi xilosa reduktase (XR) dari Scheffersomyces (Pichia) stipites, maka isolat hasil rekayasa dapat memanfaatkan xilosa untuk produksi xilitol (Oh et al, 2013).…”
Section: Fermentasi Hidrolisatunclassified
“…Several natural xylose-fermenting yeasts, such as Candida sp., Pichia stipites, Aspergillus carbonarius, Debaryomyces nepalensis, Schefferomyce stipitis and Pachysolen tannophilus, can use this co-substrate to generate xylitol [3,7,8]. Usually, Candida genus has strong ability of producing xylitol, such as Candida tropicalis and Candida guilliermondii being able to convert 90% xylose to xylitol in 24 h. However, these natural yeasts require a well-controlled supply of oxygen and are sensitive to ethanol levels, which limit their use [3]. Other species including P. stipitis and Saccharamyces cerevisiae, which are widely used as host strains, also have strong ability of production xylitol.…”
Section: Microorganisms With the Ability Of Producing Xylitolmentioning
confidence: 99%
“…At present, xylitol was mainly produced by chemical method of acidification and hydrogenation and semi-biological method of microbial fermentation of hemicellulose hydrolysate. In the semi-biological method, several natural xylose-fermenting yeasts can convert D-xylose to xylitol through reduction by a Nicotinamide Adenine Dinucleotide (Phosphate) (reduced) (NAD (P) H)-dependent xylose reductase (XR) [3]. Both of the methods rely on the hydrolysis and purification of D-xylose from hemicellulose-xylan hydrolysates.…”
Section: Introductionmentioning
confidence: 99%